Primary Malignant Mixed Müllerian Mesodermal Tumor Mimicking a Rectosigmoid Carcinoma: A Case Report and Review of the Literature - Sakshi Kapur; Levin Miles (Case Reports in Oncological Medicine)
We report a case of a 53-year-old female who presented with chronic constipation and abdominal discomfort for six months. Her past surgical history was significant for a total abdominal hysterectomy with bilateral salpingooophorectomy, performed eight years ago, for uterine fibroids and endometriosis. Workup revealed a mass measuring 5 × 4.5 × 2 cm in the rectosigmoid colon. Patient underwent a low anterior resection and a fungating, centrally ulcerated rectosigmoid mass with a positive mesorectal margin was removed. Histopathology revealed a heterologous mixed mesodermal tumor (chondroid and osteoid elements). The epithelial component was compatible with a grade 2 endometrioid adenocarcinoma. Immunohistochemical stains were supportive, with positive expression for CK7 and ER, negative for CK20, and only very focally and weakly positive for both CDX2 and p63. Chromogranin, synaptophysin, and TTF-1 were negative. Following surgery, she was treated with five cycles of carboplatin (AUC 6) and paclitaxel (175 mg/m2), followed by irradiation. Twenty-six months later, patient continues to be asymptomatic and disease-free. Mixed müllerian mesodermal tumors mimicking colorectal cancer have been reported in the past. Our case highlights the rarity and the challenges encountered in diagnosing and treating these rare tumors.